Analisis Tradisi Betimbang Anak Usia Dini Lahir Bulan Safar di Kapuas Hulu - Santi Santi; Diana Diana; Iin Maulina (Jurnal Pendidikan Anak Usia Dini dan Kewarganegaraan, 2025)
Tradition betimbang is a traditional ceremony performed for children born in the month of Safar. This tradition has been carried out for generations and is still preserved today by the local community. Betimbang tradition is a traditional ceremony performed for children born in the month of Safar. This tradition has been carried out for generations and is still preserved to this day by the local community. This research aims to analyze the contribution of local culture in early childhood learning as a character development effort. Local culture has an important role in shaping children's identity and character from an early age. The used study methodology is descriptive qualitative, using data gathering approaches such as in-depth interviews and documentation. The findings indicated that the betimbang custom is still practiced by the population of Tanjung Intan Village as a hereditary cultural legacy. This ritual is observed for children born in the month of Safar, since this month is seen undesirable. The betimbang ritual procession encompasses the phases of begansai, buang-buang, fresh flour preparation, weighing the kid with apam cake, and hair cutting. The community believes that this custom may deter youngsters from misconduct and adversity. Researchers discovered that this practice cannot serve as the only metric for children's character development; it must be supplemented by effective parenting from guardians. The betimbang tradition embodies religious principles and communal cooperation that is upheld by the local community